Editorial Board IJBB Vol. 9 No. 1 September 2021 - Wiguna, Putu Perdana Kusuma (International Journal of Biosciences and Biotechnology; Vol 9 No 1 (2021): INTERNATIONAL JOURNAL OF BIOSCIENCES AND BIOTECHNOLOGY, 2021)
Editorial Board IJBB Vol. 9 No. 1 September 2021